Interactions with soil biota shift from negative to positive when a tree species is moved outside its native range. Issue 2 (21st January 2014) - Gundale, Michael J.; Kardol, Paul; Nilsson, Marie‐Charlotte; Nilsson, Urban; Lucas, Richard W.; Wardle, David A.
Summary: Studies evaluating plant–soil biota interactions in both native and introduced plant ranges are rare, and thus far have lacked robust experimental designs to account for several potential confounding factors. Here, we investigated the effects of soil biota on growth of Pinus contorta, which has been introduced from Canada to Sweden. Using Swedish and Canadian soils, we conducted two glasshouse experiments. The first experiment utilized unsterilized soil from each country, with a full‐factorial cross of soil origin, tree provenance, and fertilizer addition. The second experiment utilized gamma‐irradiated sterile soil from each country, with a full‐factorial cross of soil origin, soil biota inoculation treatments, tree provenance, and fertilizer addition. The first experiment showed higher seedling growth on Swedish soil relative to Canadian soil. The second experiment showed this effect was due to differences in soil biotic communities between the two countries, and occurred independently of all other experimental factors. Our results provide strong evidence that plant interactions with soil biota can shift from negative to positive following introduction to a new region, and are relevant for understanding the success of some exotic forest plantations, and invasive and range‐expanding native species. Abstract : See also the Commentary by van der Putten